Science fiction before 1900 : imagination discovers technology - Alkon, Paul K. (Paul Kent) (Studies in literary themes and genres ;, 2002)
Paul Alkon analyzes several key works that mark the most significant phases in the early evolution of science fiction, including Frankenstein, Twenty Thousand Leagues Under the Sea, A Connecticut Yankee in King arthur's Court and The Time Machine. He places the work in context and discusses the genre and its relation to other kinds of literature.